ANALISIS REGRESI LOGISTIK ORDINAL FAKTOR-FAKTOR YANG MEMPENGARUHI STATUS BEASISWA MAHASISWA DI UNIVERSITAS MATARAM - Febrilia, Baiq Rika Ayu; Yani, Mi'rojatul Handa; Anwar, Syahril (PATTIMURA UNIVERSITY, 2020)
This study aims to analyze the factors that influence the status of student scholarships (get or not get a scholarship) using ordinal logistic regression analysis. The subjects involved were 100 students at Mataram University. The data used in this study are primary data collected using the Google Form online survey sheet. The research variable is the status of student scholarships as a response variable and entry path to state universities, the type of parent's occupation, the status of the Indonesia Smart Card (KIP) as its predictor variable. Each variable is divided into several categories on an ordinal scale, so that ordinal logistic regression is a solution in explaining the relationship between these variables. The results showed that the factors influencing the status of student scholarships were college entry channels and the type of parent's occupation. The relationship of these three variables is given by one logit model.